AlFoCS + F3D – II. Unexpectedly low gas-to-dust ratios in the Fornax galaxy cluster. Issue 4 (6th February 2021) - Zabel, Nikki; Davis, Timothy A; Smith, Matthew W L; Sarzi, Marc; Loni, Alessandro; Serra, Paolo; Lara-López, Maritza A; Cigan, Phil; Baes, Maarten; Bendo, George J; De Looze, Ilse; Iodice, Enrichetta; et al.
ABSTRACT: We combine observations from Atacama Large Millimeter/submillimeter Array (ALMA), Australia Telescope Compact Array, Multi Unit Spectroscopic Explorer (MUSE), and Herschel to study gas-to-dust ratios in 15 Fornax cluster galaxies detected in the FIR/sub-mm by Herschel and observed by ALMA as part of the ALMA Fornax Cluster Survey. The sample spans a stellar mass range of 8.3 ≤ log( M ⋆ /M⊙ ) ≤ 11.16, and a variety of morphological types. We use gas-phase metallicities derived from MUSE observations (from the Fornax3D survey) to study these ratios as a function of metallicity, and to study dust-to-metal ratios, in a sub-sample of nine galaxies. We find that gas-to-dust ratios in Fornax galaxies are systematically lower than those in field galaxies at fixed stellar mass/metallicity. This implies that a relatively large fraction of the metals in these Fornax systems is locked up in dust, which is possibly due to altered chemical evolution as a result of the dense environment. The low ratios are not only driven by H i deficiencies, but H2 -to-dust ratios are also significantly decreased. This is different in the Virgo cluster, where low gas-to-dust ratios inside the virial radius are driven by low H i -to-dust ratios, while H2 -to-dust ratios are increased. Resolved observations of NGC 1436 show a radial increase in H2 -to-dust ratio, and show that low ratios are present throughout the disc. We propose various explanations for the low H2 -to-dust ratios in the Fornax cluster, including the more efficient stripping of H2 compared to dust, more efficient enrichment of dust in the star formation process, and altered interstellar medium physics in the cluster environment.